Geotechnics of soft soils : focus on ground improvement : proceedings of the second International Workshop on Geotechnics of Soft Soils, Glasgow, Scotland, 3-5 September 2008 /: focus on ground improvement : proceedings of the second International Workshop on Geotechnics of Soft Soils, Glasgow, Scotland, 3-5 September 2008. (©2009) - Unknown
No abstract available